Dissemination of blaOXA-58 in Proteus mirabilis isolates from Germany. (15th January 2017) - Lange, Felix; Pfennigwerth, Niels; Gerigk, Sonja; Gohlke, Frank; Oberdorfer, Klaus; Purr, Ingvill; Wohanka, Nikolaus; Roggenkamp, Andreas; Gatermann, Sören G.; Kaase, Martin
Abstract : Objectives: Characterization of Proteus mirabilis isolates harbouring bla OXA-58 with emphasis on the genetic environment of this resistance determinant. Methods: Strains of P. mirabilis ( n  =   37) isolated from different patients were tested for the presence of bla OXA-58 . The genetic context of bla OXA-58 was determined by WGS of two strains and Sanger sequencing. Clonality of the strains was assessed by PFGE. Susceptibility testing was performed by microdilution according to EUCAST. Results: Four strains isolated in different geographical regions of Germany were positive for bla OXA-58, and WGS showed that this resistance gene was harboured on a plasmid. Sanger sequencing confirmed the presence of two nearly identical plasmids, 6219 and 6208 bp in size, in all four strains. Upstream of bla OXA-58 an IS Aba 3-like transposase gene was located. The P. mirabilis strains were not clonally related according to PFGE. MICs of meropenem for three of the strains were only just above the EUCAST breakpoint and the Carba NP test was positive for only two of the strains. Conclusions: To our knowledge, this is the first description of bla OXA-58 in the species P. mirabilis . The resistance gene is harboured by almost identical plasmids in strains not clonally related and from different geographical regions. Apart from an IS Aba 3-like transposase gene upstream of bla OXA-58 the genetic context is different from bla OXA-58 harboured on plasmids in the genus Acinetobacter . With MICs of meropenem well below the EUCAST breakpoint or only just above it and equivocal or false negative results from the Carba NP test, bla OXA-58 can be easily overlooked in P. mirabilis .